ARTIFICIAL INTELLIGENCE IN STRUCTURAL DESIGN, AN INTRODUCTION TO NEURAL NETWORKS (Collection of scientific works «Modern structures of metal and wood», 2025)
This article presents the potential application of artificial intelligence, particularly artificial neural networks (ANNs), in the design of engineering structures. The subject of the paper is the automatic recognition of the geometric shape of an arc as circular, elliptical or parabolic.  Correct identification of the arc shape is fundamental to the creation of the static scheme and computational model of the structure, which is necessary for strength analysis of the structure. This paper analyzes two identification methods based on ANN: multilayer perceptron (MLP) and convolutional neural network  (CNN).  The  MLP  network  classifies  the type  of  arc based  on  the  geometric  features  of selected points lying on the arc, while the CNN network makes recognition based on the graphical representation  of  the  arc  as  a  black and  white  image.  The  prospects  for  AI  applications  in  civil engineering are also discussed, with a focus on generative models and their potential use in the design, simulation and automation of construction processes.
Keywords: machine learning; pattern recognition; artificial neural networks; engineering structures; parabolic arc; elliptic arc; circular arc